Evaluation of Rejected Soybean Milk-Based Liquid Organic Fertilizer with Garlic and Turmeric Additives in Hydroponic Cultivation - Titik Suryani; Lina Agustina; Santhyami; Ima Aryani; Sri Darnoto; Siti Kartika Sari (Bioscientist : Jurnal Ilmiah Biologi, 2026)
This study investigated the potential use of rejected soybean milk as a raw material for producing liquid organic fertilizer (LOF) for hydroponic cultivation. The research was designed as a laboratory-based experimental study. The LOF was formulated from soybean milk waste, spent mushroom baglog, turmeric, and garlic through anaerobic fermentation. It was then characterized based on sensory and chemical properties and applied to hydroponically cultivated water spinach (Ipomoea aquatica) over a 9-week growth period. Sensory evaluation showed that the resulting LOF was a brownish-orange, free-flowing, and odorless liquid, indicating the occurrence of humification processes during fermentation. Chemical analysis revealed low macronutrient concentrations, with nitrogen, phosphorus, and potassium contents of 0.18%, 0.003%, and 0.16%, respectively. These values were below the Indonesian National Standard for liquid organic fertilizer. The LOF also had an alkaline pH of 8.32. Plant growth trials demonstrated a progressive decline in growth performance as the proportion of soybean-milk-based LOF increased. The AB Mix treatment consistently produced superior results across all growth parameters, including plant height, leaf number, and leaf size. Plants treated with the LOF generally exhibited yellowish-green leaves and reduced vegetative vigor, although survival remained 100% across all treatments. These findings indicate that rejected soybean milk can be valorized into a physically stable LOF; however, the current formulation provides insufficient plant-available nutrients and may induce plant stress due to its high pH and the potential phytotoxic effects of turmeric and garlic extracts. Further optimization through nutrient enrichment, pH adjustment, and controlled additive concentrations is therefore required to develop soybean-milk-based LOF as a viable alternative to synthetic AB Mix for hydroponic cultivation.